2015
DOI: 10.1063/1.4927187
|View full text |Cite
|
Sign up to set email alerts
|

The development of new radiation protocols for insect sterilization using long wavelength x-rays

Abstract: Abstract. Control of insect species for the protection of crops, livestock, and prevention of disease such as dengue fever and malaria is a high priority in today's global economy. Traditional methods such as pesticides have fallen out of favor because its effects are indiscriminate as well as adverse and unpredictable impacts on the environment. Modern novel techniques such as genetic modification have had trouble gaining traction due to ethics concerns and the potential for unforeseen side effects. One appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
(37 reference statements)
0
3
0
Order By: Relevance
“… Cagnotti et al (2012) used X-rays to sterilize Tuta absoluta pupae and found that 200 Gy was the best dose for sterility. Urquidi et al (2015) used different wavelengths of X-rays to irradiate mosquitos, finding that long wavelengths were more effective at mosquito sterilization. Adult orangeworm moths were irradiated with X-rays by Light et al (2015) , the research showed that 125 Gy could cause sterility in both parents and F 1 generations.…”
Section: Introductionmentioning
confidence: 99%
“… Cagnotti et al (2012) used X-rays to sterilize Tuta absoluta pupae and found that 200 Gy was the best dose for sterility. Urquidi et al (2015) used different wavelengths of X-rays to irradiate mosquitos, finding that long wavelengths were more effective at mosquito sterilization. Adult orangeworm moths were irradiated with X-rays by Light et al (2015) , the research showed that 125 Gy could cause sterility in both parents and F 1 generations.…”
Section: Introductionmentioning
confidence: 99%
“…Spermatogenesis initiates at the anterior tip of the testis where germline stem cells (GSCs) undergo successive mitosis and meiosis, and progress through spermatogonia, spermatocyte, and spermatid to produce spermatozoa [13]. Earlier stages of spermatogenesis, especially the mitotic spermatogonia and meiotic spermatocytes, are more sensitive to radiation and are more likely to experience irreversible irradiation-induced chromosomal damage and are eliminated [14]. Irradiation on spermatids and spermatozoa could also lead to dominant lethal mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Control of insect species for crop and livestock protection, as well as the prevention of diseases such as infectious diseases. Pesticides, for example, have fallen out of favor due to their indiscriminate effects as well as negative and unpredictable effects on the environment [9].…”
Section: Introductionmentioning
confidence: 99%